A Phase II Study Evaluating the Interest to Combine UCPVax, a Telomerase CD4 TH1-Inducer Cancer Vaccine, and Atezolizumab for the Treatment of HPV Positive Cancers: VolATIL Study - Rebucci-Peixoto, Magali; Vienot, Angélique; Adotevi, Olivier; Jacquin, Marion; Ghiringhelli, Francois; de la Fouchardière, Christelle; You, Benoit; Maurina, Tristan; Kalbacher, Elsa; Bazan, Fernando; Meynard, Guillaume; Clairet, Anne-Laure; et al. (Frontiers in Oncology, 2022)
Background: There is a strong rational of using anti PD-1/L1 antibodies in human papillomavirus (HPV)-induced cancers. However, anti-PD-1/L1 as monotherapy induces a limited number of objective responses. The development of novel combinations in order to improve the clinical efficacy of an anti-PD-1/L1 is therefore of interest. Combining anti-PD-1/L1 therapy with an antitumor vaccine seems promising in HPV positive (+) cancers. UCPVax is a therapeutic cancer vaccine composed of two separate peptides derived from telomerase (hTERT). UCPVax is being evaluated in a multicenter phase I/II study in NSCLC (Non-Small Cell Lung Cancer) and has demonstrated to be safe and immunogenic. The aim of the VolATIL study is to evaluate the combination of atezolizumab (an anti-PD-L1) and UCPVax vaccine in a multicentre phase II study in patients with HPV+ cancers. Methods: Patients with HPV+ cancer (anal canal, head and neck, and cervical or vulvar), at locally advanced or metastatic stage, and refractory to at least 1 line of systemic chemotherapy are eligible. The primary endpoint is the objective response rate (ORR) at 4 months. Patients will receive atezolizumab every 3 weeks at a fixed dose of 1200 mg in combination with the UCPVax vaccine at 1 mg subcutaneously. Discussion: Anti-cancer vaccines can restore cancer-immunity via the expansion and activation of tumor-specific T cells in patients lacking pre-existing anti-tumor responses. Moreover, preclinical data showed that specific TH1 CD4 T cells sustain the quality and homing of an antigen-specific CD8+ T cell immunity. In previous clinical studies, the induction of anti-hTERT immunity was significantly correlated to survival in patients with advanced squamous anal cell carcinoma. Thus, there is a strong rational to combine an anticancer hTERT vaccine and an immune checkpoint inhibitor to activate and promote antitumor T cell immunity. This pivotal proof of concept study will evaluate the efficacy and safety of the combination of a telomerase-based TH1 inducing vaccine (UCPVax) and an anti PD-L1 (atezolizumab) immunotherapy in HPV+ cancers, as well as confirming their synergic mechanism, and settling the basis for a new combination for future clinical trials. Trial registration: NCT03946358